Datasheets for Datasets. - GEBRU, TIMNIT; MORGENSTERN, JAMIE; VECCHIONE, BRIANA; VAUGHAN, JENNIFER WORTMAN; WALLACH, HANNA; III, HAL DAUMÉ; CRAWFORD, KATE (Communications of the ACM, 2021)
The authors discuss the use of datasheets for the collection and use of datasets in machine learning. They mention the need for datasheets by both data creators and data consumers, the kinds of questions that should be asked about the motivation, collection, and processing of the data, and the challenges in creating more standardized datasheets.